Spatial and temporal variation in host–parasitoid interactions: leafcutter ant hosts and their phorid parasitoids - Elizalde, Luciana (2017)
1. Parasitoid–host interactions are important components of ecological communities. Although parasitoid–host interactions are strongly shaped by evolutionary history, the abundance of both the parasitoid and the host may have a role in determining the nature of the interaction once phylogenetic relationships are considered. 2. Leafcutter ants are hosts of phorid parasitoids and represent a well-defined and specialised module within a larger network of ant–symbiont interactions. A low specificity host taxa and a positive association between host abundance and parasitoid interaction frequency were expected due to the close phylogenetic relatedness of the hosts. 3. The interactions among all species of leafcutter ants and their parasitoids were quantified in two localities with different species richness. This study also characterised the spatial-temporal variability of these interactions, determined the patterns of parasitoid specificity and host selection, and tested for an association between host abundance and parasitoid interaction frequency. 4. Contrary to expectation, most parasitoid species were highly specialised and interaction frequency for parasitoid species was not related to host abundance. All host ant species were attacked by more than one phorid species. Some phorid species used more than one host species and showed preference for the same species over space and time, suggesting that there are physiological and/or behavioural restrictions on host use. 5. These results show that there is a tendency for specialisation even when hosts are highly similar in their ecology. From a biological control perspective, these parasitoids may be effective candidates, due to the high specificity of some species and little host-use variation through time.